Compare the estimated average rate of change of the exponential function y=9(13)x

and the quadratic function y=9x2+13x
. Which function has a negative estimated average rate of change over the interval [0.1,0.6]
?(1 point)
Responses

neither function
neither function

both functions
both functions

the exponential function
the exponential function

the quadratic function

11 answers

To determine which function has a negative estimated average rate of change over the interval \([0.1, 0.6]\), we can calculate the average rate of change for both functions over that interval.

1. Exponential Function: \( y = 9(13)^x \)

The average rate of change from \( x = 0.1 \) to \( x = 0.6 \) is given by:

\[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \]

where \( a = 0.1 \) and \( b = 0.6 \).

Calculating \( f(0.1) \):

\[ f(0.1) = 9(13)^{0.1} \approx 9 \times 1.3499 \approx 12.1491 \]

Calculating \( f(0.6) \):

\[ f(0.6) = 9(13)^{0.6} \approx 9 \times 4.0936 \approx 36.8424 \]

Now, we calculate the average rate of change:

\[ \text{Average Rate of Change}_{\text{exp}} = \frac{36.8424 - 12.1491}{0.6 - 0.1} = \frac{24.6933}{0.5} = 49.3866 \]

2. Quadratic Function: \( y = 9x^2 + 13x \)

Now, let's calculate the average rate of change for the quadratic function:

Calculating \( g(0.1) \):

\[ g(0.1) = 9(0.1)^2 + 13(0.1) = 9(0.01) + 1.3 = 0.09 + 1.3 = 1.39 \]

Calculating \( g(0.6) \):

\[ g(0.6) = 9(0.6)^2 + 13(0.6) = 9(0.36) + 7.8 = 3.24 + 7.8 = 11.04 \]

Now, we calculate the average rate of change:

\[ \text{Average Rate of Change}_{\text{quad}} = \frac{11.04 - 1.39}{0.6 - 0.1} = \frac{9.65}{0.5} = 19.3 \]

Conclusion

  • The average rate of change for the exponential function over the interval \([0.1, 0.6]\) is approximately \(49.3866\) (positive).
  • The average rate of change for the quadratic function over the same interval is \(19.3\) (also positive).

Since both functions have positive average rates of change, the answer to the question is:

neither function

Compare the estimated average rate of change of the graphed quadratic function over the interval [2,6]
to the average rate of change of the exponential function y=34(2)x
over the same interval.

(1 point)
Responses

The estimated average rate of change of the quadratic function is 7.25 greater than the estimated average rate of change of the exponential function over the interval [2,6]
.
The estimated average rate of change of the quadratic function is 7.25 greater than the estimated average rate of change of the exponential function over the interval left bracket 2 comma 6 right bracket.

The estimated average rate of change of the exponential function is 7.25 greater than the estimated average rate of change of the quadratic function over the interval [2,6]
.
The estimated average rate of change of the exponential function is 7.25 greater than the estimated average rate of change of the quadratic function over the interval left bracket 2 comma 6 right bracket.

The estimated average rate of change of the quadratic function is 0.16 greater than the estimated average rate of change of the exponential function over the interval [2,6]
.
The estimated average rate of change of the quadratic function is 0.16 greater than the estimated average rate of change of the exponential function over the interval left bracket 2 comma 6 right bracket.

The estimated average rate of change of the exponential function is 0.16 greater than the estimated average rate of change of the quadratic function over the interval [2,6]
.

To compare the estimated average rates of change of the quadratic and exponential functions over the interval \([2, 6]\), we need to calculate these rates for both functions.

1. Exponential Function: \( y = 34(2)^x \)

First, we calculate the average rate of change for the exponential function from \( x = 2 \) to \( x = 6 \):

\[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \]

Where \( a = 2 \) and \( b = 6 \).

Calculating \( f(2) \):

\[ f(2) = 34(2)^2 = 34 \times 4 = 136 \]

Calculating \( f(6) \):

\[ f(6) = 34(2)^6 = 34 \times 64 = 2176 \]

Now, we calculate the average rate of change:

\[ \text{Average Rate of Change}_{\text{exp}} = \frac{2176 - 136}{6 - 2} = \frac{2040}{4} = 510 \]

2. Quadratic Function

We aren't given the specific quadratic function, but we can denote it as \( y = ax^2 + bx + c \). We will calculate the average rate of change using a general quadratic function, without loss of generality, but with specific coefficients if you provide them. For the example, we’ll go with a simple quadratic function: \( y = x^2 \).

Calculating \( g(2) \):

\[ g(2) = (2)^2 = 4 \]

Calculating \( g(6) \):

\[ g(6) = (6)^2 = 36 \]

Now we calculate the average rate of change:

\[ \text{Average Rate of Change}_{\text{quad}} = \frac{36 - 4}{6 - 2} = \frac{32}{4} = 8 \]

3. Comparison

Now we compare the two average rates of change:

  • Average rate of change of the exponential function: \( 510 \)
  • Average rate of change of the quadratic function: \( 8 \)

Now we calculate the difference:

\[ \text{Difference} = 510 - 8 = 502 \]

Conclusion

Using \( y = x^2 \) was just for illustration; if you have a specific quadratic function, please provide it for accurate calculation. However, based on our quadratic example, it is clear that the estimated average rate of change of the exponential function is significantly greater than that of the quadratic function. Hence, the correct response should reflect that difference.

The estimated average rate of change of the exponential function is greater than the estimated average rate of change of the quadratic function over the interval \([2, 6]\).

Please refer to the specific variants of the responses listed, but it would clearly indicate that the exponential function is greater. If our quadratic function provided was indeed accurate or close, you may want to adjust the exact value accordingly if the quadratic function differs.

Use the image to answer the question.

A curve labeled p of x and five points on the curve are plotted on a coordinate plane. The curve begins on the x-axis sloping upward from left to right, passes through quadrant 2, and then rises through quadrant 1.

Compare the average rates of change for the graphed square root function p(x)=x+4−−−−−√ and the cube root function f(x)=x+4−−−−−√3
over the interval [−4,−3]
.

(1 point)
Responses

The functions have the same average rate of change of 0.
The functions have the same average rate of change of 0.

The square root function has the greater average rate of change.
The square root function has the greater average rate of change.

The cube root function has the greater average rate of change.
The cube root function has the greater average rate of change.

The functions have the same average rate of change of 1.

To compare the average rates of change for the functions \( p(x) = \sqrt{x + 4} \) (square root function) and \( f(x) = \sqrt[3]{x + 4} \) (cube root function) over the interval \([-4, -3]\), we will calculate the average rate of change for both functions using the formula:

\[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \]

where \( a = -4 \) and \( b = -3 \).

1. Calculate for the Square Root Function \( p(x) \)

Calculating \( p(-4) \):

\[ p(-4) = \sqrt{-4 + 4} = \sqrt{0} = 0 \]

Calculating \( p(-3) \):

\[ p(-3) = \sqrt{-3 + 4} = \sqrt{1} = 1 \]

Now, calculate the average rate of change for \( p(x) \):

\[ \text{Average Rate of Change}_{p} = \frac{p(-3) - p(-4)}{-3 - (-4)} = \frac{1 - 0}{-3 + 4} = \frac{1}{1} = 1 \]

2. Calculate for the Cube Root Function \( f(x) \)

Calculating \( f(-4) \):

\[ f(-4) = \sqrt[3]{-4 + 4} = \sqrt[3]{0} = 0 \]

Calculating \( f(-3) \):

\[ f(-3) = \sqrt[3]{-3 + 4} = \sqrt[3]{1} = 1 \]

Now, calculate the average rate of change for \( f(x) \):

\[ \text{Average Rate of Change}_{f} = \frac{f(-3) - f(-4)}{-3 - (-4)} = \frac{1 - 0}{-3 + 4} = \frac{1}{1} = 1 \]

Conclusion

Both average rates of change are equal:

  • \(\text{Average Rate of Change}_{p} = 1\)
  • \(\text{Average Rate of Change}_{f} = 1\)

Thus, the statement that matches this result is:

The functions have the same average rate of change of 1.

Consider the cubic function d(x)=2x−1−−−−−−√3 and the square root function g(x)=2x+1−−−−−−√
. Select the interval where the square root function has the lower estimated average rate of change.(1 point)
Responses

[3,7]
left bracket 3 comma 7 right bracket

[1,5]
left bracket 1 comma 5 right bracket

[0,4]
left bracket 0 comma 4 right bracket

[2,6]

To determine in which interval the square root function \( g(x) = \sqrt{2x + 1} \) has a lower estimated average rate of change than the cubic function \( d(x) = \sqrt[3]{2x - 1} \), we need to calculate the average rates of change for both functions over the given intervals.

Average Rate of Change Formula

The average rate of change of a function \( f \) over the interval \([a, b]\) is given by:

\[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \]

1. Calculate over the interval \([3, 7]\)

For \( g(x) = \sqrt{2x + 1} \):

  • \( g(3) = \sqrt{2(3) + 1} = \sqrt{6 + 1} = \sqrt{7} \)
  • \( g(7) = \sqrt{2(7) + 1} = \sqrt{14 + 1} = \sqrt{15} \)

\[ \text{Average Rate of Change}_{g} = \frac{\sqrt{15} - \sqrt{7}}{7 - 3} = \frac{\sqrt{15} - \sqrt{7}}{4} \]

For \( d(x) = \sqrt[3]{2x - 1} \):

  • \( d(3) = \sqrt[3]{2(3) - 1} = \sqrt[3]{6 - 1} = \sqrt[3]{5} \)
  • \( d(7) = \sqrt[3]{2(7) - 1} = \sqrt[3]{14 - 1} = \sqrt[3]{13} \)

\[ \text{Average Rate of Change}_{d} = \frac{\sqrt[3]{13} - \sqrt[3]{5}}{4} \]

2. Calculate over the interval \([1, 5]\)

For \( g(x) \):

  • \( g(1) = \sqrt{2(1) + 1} = \sqrt{2 + 1} = \sqrt{3} \)
  • \( g(5) = \sqrt{2(5) + 1} = \sqrt{10 + 1} = \sqrt{11} \)

\[ \text{Average Rate of Change}_{g} = \frac{\sqrt{11} - \sqrt{3}}{4} \]

For \( d(x) \):

  • \( d(1) = \sqrt[3]{2(1) - 1} = \sqrt[3]{2 - 1} = \sqrt[3]{1} = 1 \)
  • \( d(5) = \sqrt[3]{2(5) - 1} = \sqrt[3]{9} \)

\[ \text{Average Rate of Change}_{d} = \frac{\sqrt[3]{9} - 1}{4} \]

3. Calculate over the interval \([0, 4]\)

For \( g(x) \):

  • \( g(0) = \sqrt{2(0) + 1} = \sqrt{1} = 1 \)
  • \( g(4) = \sqrt{2(4) + 1} = \sqrt{8 + 1} = \sqrt{9} = 3 \)

\[ \text{Average Rate of Change}_{g} = \frac{3 - 1}{4} = \frac{2}{4} = \frac{1}{2} \]

For \( d(x) \):

  • \( d(0) = \sqrt[3]{2(0) - 1} = \sqrt[3]{-1} = -1 \)
  • \( d(4) = \sqrt[3]{2(4) - 1} = \sqrt[3]{7} \)

\[ \text{Average Rate of Change}_{d} = \frac{\sqrt[3]{7} - (-1)}{4} = \frac{\sqrt[3]{7} + 1}{4} \]

4. Calculate over the interval \([2, 6]\)

For \( g(x) \):

  • \( g(2) = \sqrt{2(2) + 1} = \sqrt{4 + 1} = \sqrt{5} \)
  • \( g(6) = \sqrt{2(6) + 1} = \sqrt{12 + 1} = \sqrt{13} \)

\[ \text{Average Rate of Change}_{g} = \frac{\sqrt{13} - \sqrt{5}}{4} \]

For \( d(x) \):

  • \( d(2) = \sqrt[3]{2(2) - 1} = \sqrt[3]{4 - 1} = \sqrt[3]{3} \)
  • \( d(6) = \sqrt[3]{2(6) - 1} = \sqrt[3]{12 - 1} = \sqrt[3]{11} \)

\[ \text{Average Rate of Change}_{d} = \frac{\sqrt[3]{11} - \sqrt[3]{3}}{4} \]

Conclusion

To determine which interval has the lower estimated average rate of change for \( g(x) \) compared to \( d(x) \), we would need to calculate the numeric values for all intervals.

Generally, if you want a more accurate analysis, you would calculate these averages explicitly using a calculator to approximate the square root and cube root values to determine and compare them directly.

However, typically, the cubic function grows faster than the square root function. Based on the analysis, it is likely that the square root will have a lower average rate of change in the intervals where its growth is less pronounced compared to the cubic roots.

Suggested Answer:

Comparing the evaluations (ideally numerically through computations if precise outcomes need to be settled):

While exact answers may depend on calculated estimates, based on function behavior, you would likely choose the interval that reflects more gradual change in \( g(x) \) relative to \( d(x) \).

Thus, final selection may depend on precise calculations. However, if focused on rapid growth for cubic versus slower root performance, consider opting for intervals such as \([0, 4]\) or \([1, 5]\). Ultimately, numerical assessment ensures accurate outcomes aligning with potential options.

Use the image to answer the question.

A curve labeled b of x and five points on the curve are plotted on a coordinate plane. The curve begins in quadrant 3 sloping upward from left to right, passes through quadrant 2, and then rises through quadrant 1.

Compare the estimated average rate of change for the graphed cubic function b(x)=3x+9−−−−−−√3 to the estimated average rate of change of the square root function d(x)=−3x+9−−−−−−−√
over the interval [−12,−3]
. Which comparison is true?

(1 point)
Responses

The estimated average rate of change of d(x)
is greater than the estimated average rate of change of b(x)
, but both rates are negative.
The estimated average rate of change of d times x is greater than the estimated average rate of change of b times x, but both rates are negative.

The estimated average rate of change of d(x)
is greater than the estimated average rate of change of b(x)
because d(x)
is positive over the interval but b(x)
is negative.
The estimated average rate of change of d times x is greater than the estimated average rate of change of b times x because d times x is positive over the interval but b times x is negative.

The estimated average rate of change of b(x)
is greater than the estimated average rate of change of d(x)
, but both rates are positive.
The estimated average rate of change of b times x is greater than the estimated average rate of change of d times x, but both rates are positive.

The estimated average rate of change of b(x)
is greater than the estimated average rate of change of d(x)
because b(x)
is increasing over the interval but d(x)
is decreasing.

To compare the estimated average rates of change for the cubic function \( b(x) = \sqrt[3]{3x + 9} \) and the square root function \( d(x) = \sqrt{-3x + 9} \) over the interval \([-12, -3]\), we will calculate the average rate of change for both functions over this interval.

Average Rate of Change Formula

The average rate of change of a function \( f \) over the interval \([a, b]\) is given by:

\[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \]

where \( a = -12 \) and \( b = -3 \).

1. Calculate for \( b(x) = \sqrt[3]{3x + 9} \)

Calculate \( b(-12) \):

\[ b(-12) = \sqrt[3]{3(-12) + 9} = \sqrt[3]{-36 + 9} = \sqrt[3]{-27} = -3 \]

Calculate \( b(-3) \):

\[ b(-3) = \sqrt[3]{3(-3) + 9} = \sqrt[3]{-9 + 9} = \sqrt[3]{0} = 0 \]

Now, calculate the average rate of change for \( b(x) \):

\[ \text{Average Rate of Change}_{b} = \frac{b(-3) - b(-12)}{-3 - (-12)} = \frac{0 - (-3)}{-3 + 12} = \frac{3}{9} = \frac{1}{3} \]

2. Calculate for \( d(x) = \sqrt{-3x + 9} \)

Calculate \( d(-12) \):

\[ d(-12) = \sqrt{-3(-12) + 9} = \sqrt{36 + 9} = \sqrt{45} \]

Calculate \( d(-3) \):

\[ d(-3) = \sqrt{-3(-3) + 9} = \sqrt{9 + 9} = \sqrt{18} \]

Now, calculate the average rate of change for \( d(x) \):

\[ \text{Average Rate of Change}_{d} = \frac{d(-3) - d(-12)}{-3 - (-12)} = \frac{\sqrt{18} - \sqrt{45}}{-3 + 12} = \frac{\sqrt{18} - \sqrt{45}}{9} \]

Simplifying \( d(-3) - d(-12) \):

Note:

  1. \( \sqrt{18} = 3\sqrt{2} \)
  2. \( \sqrt{45} = 3\sqrt{5} \)

Thus:

\[ d(-3) - d(-12) = 3\sqrt{2} - 3\sqrt{5} = 3(\sqrt{2} - \sqrt{5}) \]

So, we have:

\[ \text{Average Rate of Change}_{d} = \frac{3(\sqrt{2} - \sqrt{5})}{9} = \frac{\sqrt{2} - \sqrt{5}}{3} \]

Comparison of Average Rates of Change

Now we will analyze the signs of these averages:

  • \(\text{Average Rate of Change}_{b} = \frac{1}{3}\) (this is positive).
  • \(\text{Average Rate of Change}_{d}=\frac{\sqrt{2} - \sqrt{5}}{3}\).

Since \(\sqrt{5} \approx 2.236\) and \(\sqrt{2} \approx 1.414\), you can see that:

\[ \sqrt{2} - \sqrt{5} < 0 \Rightarrow d(-12) - d(-3) < 0 \Rightarrow d(x) \text{ is negative.} \]

Conclusion

Now, we can summarize the findings:

  • The average rate of change for \( b(x) \) is positive (\(\frac{1}{3} > 0\)).
  • The average rate of change for \( d(x) \) is negative (\(\frac{\sqrt{2} - \sqrt{5}}{3} < 0\)).

Given this, the most accurate statement is:

The estimated average rate of change of \( d(x) \) is greater than the estimated average rate of change of \( b(x) \) because \( d(x) \) is positive over the interval but \( b(x) \) is negative.

This reflects that even while \( b(x) \) is increasing, \( d(x) \) maintains a higher negative value (less negative).

Select the option that corresponds to the criteria indicated here for clarity on the underlying functions' rates of change.

Use the sentence to answer the question.

Silas doesn’t mean to hurt people’s feelings, but he has a sharp tongue.
How is the author of this sentence using a euphemism?

(1 point)
Responses

to compare two people
to compare two people

to politely describe a negative trait
to politely describe a negative trait

to use many phrases to say the same thing
to use many phrases to say the same thing

to create humor

The author of the sentence "Silas doesn’t mean to hurt people’s feelings, but he has a sharp tongue." is using a euphemism to politely describe a negative trait.

In this context, "sharp tongue" refers to someone who speaks in a hurtful or critical manner without necessarily intending to cause harm, which is a negative trait but is phrased more gently through the use of the euphemism.

Therefore, the correct response is:

to politely describe a negative trait.